On Nonuniform Polynomial Trichotomy of Linear Discrete-Time Systems in Banach Spaces - Zhi-gang Li; Xiao-qiu Song; Xiu-li Yang (Journal of Applied Mathematics)
We study two nonuniform polynomial trichotomy concepts for linear discrete-time systems in Banach spaces. Our main objective is to give summation property for nonuniform polynomial trichotomies. As for applications we obtain characterization of these concepts in terms of Lyapunov functions.